NeuroExercise: The Effect of a 12-Month Exercise Intervention on Cognition in Mild Cognitive Impairment—A Multicenter Randomized Controlled Trial - Stuckenschneider, Tim; Sanders, Marit L.; Devenney, Kate E.; Aaronson, Justine A.; Abeln, Vera; Claassen, Jurgen A. H. R.; Guinan, Emer; Lawlor, Brian; Meeusen, Romain; Montag, Christian; Olde Rikkert, Marcel G. M.; Polidori, M. Cristina; et al. (Frontiers in Aging Neuroscience, 2021)
Exercise intervention studies in Mild Cognitive Impairment (MCI), a prodromal stage of AD, have demonstrated inconsistent yet promising results. Addressing the limitations of previous studies, this trial investigated the effects of a 12-month structured exercise program on the progression of MCI. The NeuroExercise study is a multicenter randomized controlled trial across three European countries (Ireland; Netherlands; Germany). 183 individuals with amnestic MCI were included and were randomized to a 12-month exercise intervention (3 units of 45 minutes) of either aerobic exercise (AE; n=60), stretching and toning exercise (ST; n=65) or to a non-exercise control group (CG; n=58). The primary outcome, cognitive performance, was determined by an extensive neuropsychological test battery. For the primary complete case (CC) analyses, between-group differences were analyzed with analysis of covariance under two conditions: 1) the exercise group (combined AE and ST groups) compared to the CG and 2) AE compared to ST. Primary analysis of the full cohort (n=166, 71.5 years; 51.8% females) revealed no between-group differences in composite cognitive score (mean difference [95% CI]), 0.12([-0.03, 0.27], p=0.13) or in any cognitive domain or quality of life. V̇O2peak was significantly higher in the exercise group compared to the CG after 12 months (-1.76([-3.39, -0.10], p=0.04). Comparing the two intervention groups revealed a higher V̇O2peak level in the aerobic exercise compared to the stretching and toning group, but no differences for the other outcomes. A 12-month exercise intervention did not change cognitive performance in individuals with amnestic MCI in comparison to a non-exercise CG. An intervention effect on physical fitness was found, which may be an important moderator for long term disease progression and warrants long-term follow-up investigations. Trial registration number NCT02913053; https://clinicaltrials.gov/ct2/show/NCT02913053